The Internal Migration of the Immigrant and Native-Born populations in Canada between 1976 and 1996 - Grenier, Gilles (Université d'Ottawa | University of Ottawa, 2003)
International immigration has changed not only the ethnic and cultural composition of the Canadian society, but it has also altered its geographical dispersion. Immigrants tend to locate in the major urban areas and thus contribute to accentuate the geographic concentration of the population. Some immigrants go to less populated areas, but many do not stay. The purpose of this paper is to look at the internal migration patterns of immigrants after they arrive in Canada and to compare them to those of the Canadian-born population. The study uses data from the four Canadian censuses of 1981, 1986, 1991 and 1996. The dependent variable is the probability of a migration during the five years that precede each census. Two variants are considered: (1) mobility between provinces and (2) mobility within and between provinces with an ordered choice model. The independent variables are the usual ones related to human capital and characteristics of the regions. Some of the results are: immigrants are on average less mobile than the Canadian-born, except at the local level; however, immigrants are more mobile than the Canadians who still live in their province of birth; mobility between provinces has decreased between 1976 and 1996; immigrants respond in a different way than the Canadian-born to some of the variables that determine mobility; immigrants tend to leave in larger proportions than the Canadian-born the provinces where there are few immigrants. / Migration interne des immigrants et des Canadiens de naissance entre 1976 et 1996. L’immigration internationale a changé non seulement la composition ethnique et culturelle de la population canadienne, mais aussi sa répartition géographique. Les immigrants ont tendance à se localiser dans les grands centres urbains et contribuent à accentuer la concentration géographique. Certains immigrants vont dans des régions moins peuplées, mais plusieurs n’y restent pas. Cette étude a pour but d’analyser les facteurs qui déterminent les migrations internes des immigrants et de comparer leur comportement à ceux des Canadiens de naissance. L’étude utilise les données des quatre recensements canadiens de 1981, 1986, 1991 et 1996. La variable dépendante est la probabilité d’une migration interne durant les cinq années précédant chaque recensement. Deux variantes sont considérées: 1) le déplacement entre provinces et 2) le déplacement à l’intérieur et entre les provinces avec un modèle de choix ordonnés. Les variables indépendantes sont les variables habituelles reliées au capital humain et aux caractéristiques des régions. Certains des résultats sont: les immigrants sont en moyenne moins mobiles que les Canadiens de naissance, sauf au niveau local; cependant, les immigrants sont plus mobiles que les Canadiens qui habitent toujours dans leur province de naissance; la mobilité entre provinces a diminué entre 1976 et 1996; les immigrants répondent de façon différente des Canadiens de naissances à certaines des variables qui déterminent la mobilité interne; les immigrants ont tendance à quitter en proportions plus grandes que les Canadiens de naissance les régions où il y a peu d’immigrants.
Keywords: Immigrants; Canada; internal migration; mobility; provinces; Immigrants; Canada; Migration interne; mobilité; provinces